The Practice of Paradiplomacy in Cooperation between the Yogyakarta Special Region Government and the Singapore International Foundation in the Education Sector - Eva Yusnita Chandra (Universitas Medan Area, 2022)
This article aims to find out how the collaborative practices that occur between the Provincial Government of the Special Region of Yogyakarta (DIY) and the Singapore International Foundation (SIF) in the field of education. DIY is a province known as the